2022
DOI: 10.1007/s00265-022-03158-w
|View full text |Cite
|
Sign up to set email alerts
|

Shorter effective lifespan in laboratory populations of D. melanogaster might reduce sexual selection

Abstract: The role of sexual selection in mediating levels of sexual conflict has been demonstrated in many experimental evolution studies on Drosophila spp. where competition among males for mating was the target of selection. Sexual selection has also been shown to affect the evolution of life-histories. However, the influence of divergent life-histories on reproductive strategies and, therefore, sexual selection and possibly sexual conflict has been less well studied. We examined D. melanogaster populations selected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…However, if expression of MHR leads to reduction in reproductive cost in general, detecting cost of MHR per se might be difficult. Alternatively, cost of MHR can be indirectly inferred from the evolutionary reduction in MHR when selection on such traits is removed (11,24) (25,26). In a similar study, we showed reduction in mate mating behaviour, including mate harming ability (27).…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…However, if expression of MHR leads to reduction in reproductive cost in general, detecting cost of MHR per se might be difficult. Alternatively, cost of MHR can be indirectly inferred from the evolutionary reduction in MHR when selection on such traits is removed (11,24) (25,26). In a similar study, we showed reduction in mate mating behaviour, including mate harming ability (27).…”
Section: Introductionsupporting
confidence: 64%
“…Several experimental evolution studies have shown the evolution of MHR (2,(10)(11)(12)(13)(14)16,17,24,38). Of these, only two have directly connected evolution of conflict related traits to life history traits such as, condition, adult lifespan, development time, and size (17,39). Though evolution of MHR is important for a population's survival (40), continuation of sexual selection (41), and maintenance of genetic variation (42), it cannot evolve in the vacuum of sexually antagonistic traits only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an independent investigation on a similar set of experimentally evolved populations (Ghosh and Joshi 2012;Mital et al 2021Mital et al , 2022 found that the intensity of sexual selection and the degree of interlocus sexual conflict to be lower in populations selected for faster development and early reproduction. The parallel between our results and those of Ghosh and Joshi (2012) and Mital et al (2021Mital et al ( , 2022 is somewhat expected, and is a robust proof in support of our theory. However, even more interesting is the difference.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, traits that inflict mate harm, i.e., the sexually antagonistic male traits, are energetically expensive to express and hence, increase in such traits is constrained by trade-offs involving costly life history traits (Wedell et al 2006;Bonduriansky et al 2008;Adler and Bonduriansky 2014;Lemaître et al 2020). Thirdly, survivorship pattern and scheduling of reproduction can also put additional constraints on the evolution of mate harm, for example by restricting mating system and breeding ecology (Mital et al 2021(Mital et al , 2022. The latter two theories are a more recent development in the field and we focus on them in the present investigation.…”
Section: Introductionmentioning
confidence: 99%